2013
DOI: 10.1016/j.pscychresns.2013.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical abnormalities in unmedicated bipolar depression and mania: A 2D 1H MRS investigation

Abstract: The neurobiology and neurochemistry of bipolar disorder and its different phases is poorly understood. This study investigated metabolite abnormalities in both unmedicated bipolar depression as well as mania using 2D 1H Magnetic Resonance Spectroscopy Imaging (MRSI). MRSI data was obtained from 24 unmedicated Bipolar Disorder (BP) subjects (12 (hypo)manic (BPM)) and 12 depressed (BPD)), and 20 closely matched healthy controls. 2D 1H MRSI data was collected from a 15 mm axial slice placed along the AC-PC line t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
51
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 45 publications
4
51
0
2
Order By: Relevance
“…Therefore, in order to better understand the brain metabolism changes in the subregions of gray matter on patients with BDd and UDd, participants with un-medicated BDd patients and UDd patients were enrolled in this study. The methodology of using a ratio of one cerebral metabolism compared with other metabolite was applied in earlier studies, just like Cho/Cr ratios21330, NAA/Cr ratios26, or Glx/Cr ratios2, etc However, they could not accurately reflect the change of cerebral metabolite concentrations30. Recent results revealed that using ratio rather than absolute concentration levels of metabolites was a technical limitation23.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, in order to better understand the brain metabolism changes in the subregions of gray matter on patients with BDd and UDd, participants with un-medicated BDd patients and UDd patients were enrolled in this study. The methodology of using a ratio of one cerebral metabolism compared with other metabolite was applied in earlier studies, just like Cho/Cr ratios21330, NAA/Cr ratios26, or Glx/Cr ratios2, etc However, they could not accurately reflect the change of cerebral metabolite concentrations30. Recent results revealed that using ratio rather than absolute concentration levels of metabolites was a technical limitation23.…”
Section: Discussionmentioning
confidence: 99%
“…The methodology of using a ratio of one cerebral metabolism compared with other metabolite was applied in earlier studies, just like Cho/Cr ratios21330, NAA/Cr ratios26, or Glx/Cr ratios2, etc However, they could not accurately reflect the change of cerebral metabolite concentrations30. Recent results revealed that using ratio rather than absolute concentration levels of metabolites was a technical limitation23. Hence, we combined the 2D-MRSI (magnetic resonance spectroscopy imaging) and LCModel software2122 in gray matter areas to measure the absolute concentration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although one study (Xu et al 2013) found no significant difference in ACC glutamate or Glx between unmedicated adults with BD and healthy adults, two other studies (Michael et al 2003;Ongur et al 2008) reported higher Glx in the prefrontal cortex of medicated adults with BD-mania; however glutamate differences in the latter studies were not significant (Ongur et al 2008). In addition to these studies conducted with adult populations, there exist only a few studies using MRS to examine ACC glutamate and/or Glx in adolescents.…”
Section: Discussionmentioning
confidence: 97%